Caliph Omar bin Abdul Aziz and Human Rights (H101-H99) (Islamic Sciences Journal, 2023)
ABSTRACT              Caliph Omar bin Abdul Aziz acceded a noble position in our Islamic history, which  is only attained by  the best leaders, conquerors, and magnificent imams of knowledge and geniuses of writers and poets. Your wonder increases when you know that he occupied this position with two years and a few months spent as a caliph for the Muslims, while other caliphs and leaders spent tens of years without recording any history, because their years of ruling were empty in the history of their nation, so people did not see any change in their lives, nor did they rise in their state . People did not feel a change in their lives, nor a rise in their state, nor an improvement in their livelihood, nor a sense of security pervading their country. Omar bin Abdul Aziz was one of those who entered history with his great works and fair administration of the state, until renewing hope in the souls that it is possible to return the ruling of the rightly caliphs as a tangible reality, not as stories that are told, no aspirations required, or imagination imagined, but as a fact that people  can witness and enjoy their goodness